The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1128/aac.50.1.286-293.2006
|View full text |Cite
|
Sign up to set email alerts
|

Multiple-Dose Pharmacokinetics and Safety of the New Antifungal Triazole BAL4815 after Intravenous Infusion and Oral Administration of Its Prodrug, BAL8557, in Healthy Volunteers

Abstract: BAL8557 is the water-soluble prodrug of BAL4815, a new broad-spectrum antifungal. Healthy male subjects were randomly assigned to four treatment cohorts to receive multiple oral doses or multiple 1-h constant-rate intravenous infusions of BAL8557. Loading doses of BAL8557 were equivalent to 100 mg (followed by oncedaily maintenance doses of 50 mg) or 200 mg (followed by once-daily maintenance doses of 100 mg) of BAL4815. In each cohort, six subjects received active drug and two subjects received the placebo. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
124
1
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(139 citation statements)
references
References 12 publications
11
124
1
3
Order By: Relevance
“…In studies of healthy volunteers, isavuconazole has been shown to be well tolerated and to have a low clearance, large volume of distribution, high bioavailability, and long elimination half-life (20,31). The present study extends these data to provide PK parameters for two high-and low-dose regimens of i.v.…”
Section: Discussionsupporting
confidence: 55%
“…In studies of healthy volunteers, isavuconazole has been shown to be well tolerated and to have a low clearance, large volume of distribution, high bioavailability, and long elimination half-life (20,31). The present study extends these data to provide PK parameters for two high-and low-dose regimens of i.v.…”
Section: Discussionsupporting
confidence: 55%
“…Pharmacokinetic parameters of isavuconazole measured in this study after a single oral dose or IV infusion of the prodrug were comparable to those obtained in a previous isavuconazole phase 1 study 13. In the current study unchanged isavuconazole was eliminated predominately via feces (33% of total drug dose recovered), and less than 1% of the dose recovered in urine was unchanged isavuconazole.…”
Section: Discussionsupporting
confidence: 83%
“…Both the prodrug and the BAL8728 cleavage product lack oral bioavailability, but isavuconazole is absorbed readily, and, relative to IV isavuconazonium sulfate (determined by isavuconazole AUC), bioavailability is 98% 7, 13. The pharmacokinetic (PK) properties of isavuconazole are linear and dose proportional 13.…”
mentioning
confidence: 99%
“…This compound can be administered either orally or intravenously as a prodrug, which then is converted by plasma esterases into the active component (3)(4)(5)(6). Previous in vitro studies have demonstrated potent antifungal activity against both common and uncommon fungal pathogens, including Candida, Aspergillus, non-Candida yeasts, and non-Aspergillus molds (7)(8)(9)(10)(11)(12)(13)(14)(15).…”
mentioning
confidence: 99%